2014
DOI: 10.5713/ajas.2014.14145
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction between Ras Homolog Enriched in Brain and FK506 Binding Protein 38 in Cashmere Goat Fetal Fibroblast Cells

Abstract: Ras homolog enriched in brain (Rheb) and FK506 binding protein 38 (FKBP38) are two important regulatory proteins in the mammalian target of rapamycin (mTOR) pathway. There are contradictory data on the interaction between Rheb and FKBP38 in human cells, but this association has not been examined in cashmere goat cells. To investigate the interaction between Rheb and FKBP38, we overexpressed goat Rheb and FKBP38 in goat fetal fibroblasts, extracted whole proteins, and performed coimmunoprecipitation to detect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In previous studies, we have confirmed the interactions between Rheb and FKBP38 experimentally in goat cells (Wang et al, 2014). In the present study, we showed that KBP38 gene-silencing induced phosphorylation of mTOR, S6, and 4EBP1.…”
Section: Discussionsupporting
confidence: 74%
“…In previous studies, we have confirmed the interactions between Rheb and FKBP38 experimentally in goat cells (Wang et al, 2014). In the present study, we showed that KBP38 gene-silencing induced phosphorylation of mTOR, S6, and 4EBP1.…”
Section: Discussionsupporting
confidence: 74%
“…Then, equivalent amounts of protein lysate were incubated with anti-4EBP1 (1:50) or anti-His (1:50) (negative control) and inactive resin (negative control) in Millipore catch-and-release spin columns. Equivalent amounts of protein lysate were also evaluated by Western blot as a positive control for 4EBP1 and PPARγ, per reported methods. , …”
Section: Methodsmentioning
confidence: 99%
“…An 1147 bp fragment of SQSTM1/p62 gene cDNA was subcloned into pGADT7 Vector (Clontech Laboratorie, Inc.) to generate the pGADT7-SQSTM1/p62 plasmid (expressing the prey protein GAL4AD-SQSTM1/p62). The pGBKT7-FKBP38 (expressing the bait protein GAL4BD-FKBP38) was described previously (Wang et al 2014). The plasmids pGADT7-SQSTM1/p62 and pGBKT7-FKBP38 were co-transferred into the Y2HGold yeast strain.…”
Section: Yeast Two-hybrid Analysis Of Protein Interactionmentioning
confidence: 99%